KARAKTERISTIK BANK LIKUIDASI DAN RESTRUKTURISASI DI INDONESIA - Siswantoro, Dodik (UI Scholars Hub, 2004)
Monetary crisis, which leads to unstable economic condition, has caused a number of banks being liquidated. This research is conducted by using major accounting ratios in order to identify the characteristics of liquidated and restructured banks, of which are listed in Jakarta Stock Exchange. The growth of bank industry was highly related with Paket Oktober 1988. This condition is marked by increasing number of banks, from 40 companies in 1988 to 240 companies in 1994. This research is conducted based on a three period financial information, commencing 1994 to 1996. Proven hypothesis concludes that the number of restructured banks is greater than of liquidated banks. On the other hand, the hypothesis related to leverage and gain has failed to be proven. However, the big sample that can be analyzed through boxplot may be the caused to this result.